Limeryki, czyli przykład poezji niepoważnej - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article discusses Polish limericks. It shows that authors’ invention can affect different aspects o f a piece, and can be noticed on the auditory level, in startling rhymes and neologisms invented by the author, as well as in the employment of humorous topics and surprising (often absurd) plot solutions. The article also shows that the primary function of limericks is that of entertaining both their authors and audiences. That is why limericks can be labelled ‘lightweight poetry’.